Language ideology and kadongo kamu flow. Issue 3 (14th September 2016) - Pier, David
Abstract: Kadongo kamu is a Ugandan guitar-based genre recognisable by its dense storytelling lyrics in Luganda language. This article offers a close analysis of kadongo kamu musical style, focusing on the interface between speech rhythm and musical rhythm. The style's poetic-musical 'flow' to be structurally analysed is interpreted with reference to a historically evolved language ideology which construes Luganda to be exceptionally 'rich' and 'deep'. I show how specific musical techniques are used to foreground aspects of Luganda that speakers prize as elegant and learned. This musical artistry enhances listeners' impressions of the proverb-rich 'deep Luganda' poetry for which kadongo kamu singers are famous.